2019
DOI: 10.3390/brainsci9050119
|View full text |Cite
|
Sign up to set email alerts
|

Target Size Manipulations Affect Error-Processing Duration and Success Perceptions but not Behavioural Indices of Learning

Abstract: We evaluated if and how success perceptions, through target size manipulations, impact processes related to motor learning. This work was based on recent literature suggesting that expectations and self-efficacy exert a direct impact on learning. We measured arousal, kinematics, learner expectancies, motivation, and outcomes in a dart-throwing task. Novices (n = 29) were assigned to either a “Large-target” (horizontal target, 10-cm high) or “Small-target” (2-cm high) group for practice (t = 90), and both group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Furthermore, the target size may have further influenced movement mechanics and the EF effect. For example, throwing at a 1cm wide-target (i.e., bullseye of a dartboard) requires greater precision than throwing at a 12.5cm target (Kranjenbrink et al, 2018) and could therefore result in greater movement variability to select the correct motor response (Ong, Hawke, & Hodges, 2019). Whilst an IF may aid precision by freezing degrees of motor freedom (e.g., reducing movement variability); in general, an IF is detrimental to motor learning (e.g., movement reinvestment; Masters & Maxwell 2008;Poolton et al, 2006).…”
Section: Developmental Factors and Task Constraintsmentioning
confidence: 99%
“…Furthermore, the target size may have further influenced movement mechanics and the EF effect. For example, throwing at a 1cm wide-target (i.e., bullseye of a dartboard) requires greater precision than throwing at a 12.5cm target (Kranjenbrink et al, 2018) and could therefore result in greater movement variability to select the correct motor response (Ong, Hawke, & Hodges, 2019). Whilst an IF may aid precision by freezing degrees of motor freedom (e.g., reducing movement variability); in general, an IF is detrimental to motor learning (e.g., movement reinvestment; Masters & Maxwell 2008;Poolton et al, 2006).…”
Section: Developmental Factors and Task Constraintsmentioning
confidence: 99%
“…EE has also been associated with positive affect (e.g., positive feelings) due to its link with dopamine release, which contributes to the consolidation of motor memories and readies the motor system for effective goal-action coupling (Sugawara, Tanaka, Okazaki, Watanabe, & Sadato, 2012;Wulf & Lewthwaite, 2016). However, some studies indicate that enhancing expectancies has not always benefited motor performance and learning (e.g., Ong, Hawke, & Hodges, 2019;Ong & Hodges, 2018). Similarly, conditions which support an individual's need for autonomy (AS) have been positively correlated with self-efficacy for motor tasks (Lemos, Wulf, Lewthwaite, & Chiviacowsky, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, previous studies showed improved success perception when learning involved lower difficulty goals (Ong, Hawke & Hodges, 2019) and even better learning than difficult goals (Iwatsuki & Regis, 2020). However, Carvalhais et al (2021) showed that learning is better when perceived competence is high.…”
Section: Discussionmentioning
confidence: 79%